Улетают - улетели: стихи / Е. А. Благинина ; худож. С. Остров - Благинина Елена Александровна (Малыш, 1982)
Экземпляры: аб ДБ (19830101) / Инвентарный номер: 6537z1 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 68 / ББК: 84(2Рос=Рус)6